Modified SEPIC Converter Performance for Grid-connected PV Systems under Various Conditions - Rizky Ajie Aprilianto; Subiyanto Subiyanto; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Step-up converter is widely used to increase DC voltage level on PV systems either off-grid or grid connected. One of the step-up converters often used in PV systems is SEPIC converter. To improve its performance, many SEPIC converters have been modified. However, performance on various conditions has not been further investigated. In this study, the modified SEPIC converter was investigated under various change conditions for grid-connected PV applications. This converter was modelled and simulated using PSIM software. The modified SEPIC converter received input from PV array 15 kWp, and its output was connected to the three-phase inverter with grid and load. The irradiance level and ambient temperature were varied to test its performance and compared to Boost converter and SEPIC converter. For all tests, the performance of modified SEPIC converter was better than other step-up converters because it was able to rectify the quality of output voltage and more efficient.